ಮೈಸೂರು ವಿಶ್ವವಿದ್ಯಾಲಯ ವಿಶ್ವಕೋಶ : ಕನ್ನಡ ವಿಶ್ವಕೋಶ - ಸಂಪುಟ ೫ - (:unkn) unknown (University of Mysore)
This Encyclopedia will help us to learn about human eyes, sight issue and other problems of eyes, human hair and other various aspects
Mysuru Vishwavidyalaya Kannada Vishwakosha Vol – 5
Keywords: Kannada; Encyclopedia; Kannada